Visual search at isoluminance: evidence for enhanced color weighting in standard sub-set and preview-based visual search. - Braithwaite, J; Watson, D; Andrews, L; Humphreys, G (2010)
Isoluminant displays depend on responses from the parvocellular visual stream, known to code color information. We examined the influence of isoluminance on attentional guidance by color using two procedures: (i) color sub-set search (Egeth, Virzi, and Garbart, 1984) and (ii) preview search (Watson and Humphreys, 1997). We used displays that do not generate a sub-set search advantage with luminant stimuli. Despite this, a sub-set search advantage was present for small color groups with isoluminant displays. Under preview-search conditions, presenting items at isoluminance amplified the effects of a negative color carry-over from a preview display to a new target, but only when there was an extended preview duration. Both findings demonstrate that presenting items at isoluminance increases the influence of color on visual search. Collectively, the data are consistent with the notion of a flexible inhibitory mechanism that can change the weighting applied to visual features in search.